I blame you, I hear you: Couples' pronoun use in conflict and dyadic coping. (November 2021) - Meier, Tabea; Milek, Anne; Mehl, Matthias R.; Nussbeck, Fridtjof W.; Neysari, Mona; Bodenmann, Guy; Martin, Mike; Zemp, Martina; Horn, Andrea B.
In dyadic interaction, a verbal focus on one individual ("you-talk, " "I-talk"), rather than on the couple ("we-talk") has predominantly been linked to dysfunctional relationship processes. However, context differences in these links have not yet been systematically examined. Is it functional to asymmetrically focus on one partner during support interactions but problematic during conflict? Does a high level of couple-focus represent a resource across contexts? In this preregistered study, we investigated dyad-level pronoun use (we-/I-/you-talk) and their link to situational relationship functioning (SRF) across three interaction tasks (one conflict, two dyadic coping tasks) within couples ( N = 365). More specifically, we examined associations of couple-means, i.e. pronoun use as a shared resource/vulnerability between partners, and couple-differences, i.e. functional/dysfunctional asymmetric pronoun use with observed interaction positivity and relationship climate. Results revealed both context differences and similarities. Asymmetric partner-focus (i.e. you-talk) was dysfunctional in conflict, whereas asymmetric partner- and self-focus (i.e., you-talk/I-talk; focus on the stressed partner) were functional in dyadic coping. Beyond asymmetry, you-talk (couple-mean) showed consistent negative associations with SRF in all tasks studied. We-talk (couple-mean) was positively linked to SRF, but only in conflict interactions. In conflict, couple-focus thus represented a shared resource that can buffer from dysfunctional conflict interaction characterized by partner-focus. In line with conceptual frameworks, the dyadic coping results emphasize the importance of focusing on the partner in need. The study corroborates the prospect of pronoun use as a context-specific indicator of relationship functioning. Gender differences, implications for future research and possible interventions are discussed.